Increased unsaturated fatty acid production associated with a suppressor of the fabA6(Ts) mutation in Escherichia coli. - Rock, C O (1996)
Plasmids that corrected the temperature-sensitive unsaturated fatty acid auxotrophy of strain M6 [fabA6 (Ts)] were isolated from an Escherichia coli genomic library. Subcloning and physical mapping localized the new gene (called sfa for suppressor of fabA) at 1,070 kb on the E. coli chromosome. DNA sequencing revealed the presence of a 227-bp open reading frame which directed the synthesis of a peptide of approximately 8 kDa, which correlated with the correction of the fabA6(Ts) phenotype. However, the sfa gene was an allele-specific suppressor since plasmids harboring the sfa gene corrected the growth phenotype of fabA6(Ts) mutants but did not correct the growth of fabA2(Ts) or fabB15(Ts) unsaturated fatty acid auxotrophs. Overexpression of the sfa gene in fabA6(Ts) mutants restored unsaturated fatty acid content at 42 degrees C, and overexpression in wild-type cells resulted in a substantial increase in the unsaturated fatty acid content of the membrane. Thus, the suppression of the fabA6(Ts) mutation by sfa was attributed to its ability to increase the biosynthesis of unsaturated fatty acids.